One minute of stair climbing and descending reduces postprandial insulin and glucose with 3-min improving insulin resistance following a mixed meal in young adults: A randomized controlled crossover trial - Jeff M. Moore; Hannah Salmons; Cameron Vinoskey; Shirin Hooshmand; Jochen Kressler (Elsevier, 2024)
Background: Glycemic markers, including postprandial glucose, insulin, and insulin resistance, are strong predictors of morbidity and mortality in individuals with and without diabetes. Stair-climbing and -descending (SCD) at a comfortable pace for 3 minutes after a sugary beverage (300 kilocalories; 100% carbohydrate) lowers insulin, with insulin sensitivity improving in 10 minutes. If similar benefits are seen following consumption of a mixed meal is unknown. We hypothesize SCD will improve these markers in a dose-response manner following a mixed meal. Methods: In a randomized, controlled, crossover trial, young adults (N = 31) performed SCD for 0 (seated control), 1, 3, and 10 minutes after a mixed meal (650 kilocalories; 53% carbohydrates, 33% fat, and 14% protein). Differences in glucose, insulin, and insulin sensitivity (ISI) from baseline to 30 min were analyzed using a mixed-effects ANOVA. Results: A significant fixed-effect was found for change in glucose [F(2.551,67.17) = 4.724,p = 0.007)], insulin [F(2.692,74.49) = 11.28,p < 0.001)], and ISI [F(2.127,56.00) = 5.848,p = 0.004)]. Compared to the seated control (0 minutes), changes in glucose were lower after 1 minute (−14.0 (−7.2)mg/dL,p < 0.001), 3 minutes (−18.4 (−7.0)mg/dL,p = 0.0007), and 10 minutes (−10.0 (−8.1)mg/dL,p = 0.039); changes in insulin were lower after 1 minute (−1.8 (−0.9)μIU/mL,p = 0.0011), 3 minutes (−2.8 (−0.9)μIU/mL,p < 0.001), and 10 minutes (−1.1 (−0.9)μIU/mL,p = 0.033); and changes in ISI were significantly higher after 3 minutes (2.4 (1.5),p < 0.001) and 10 minutes (1.3 (1.6),p = 0.014) but not 1 minute (1.2 (1.5),p = 0.059). Conclusion: Postprandial glucose and insulin improved with 1 minute, and insulin resistance improved with 3 minutes, of SCD at a self-selected, comfortable pace, after consumption of a mixed meal in apparently healthy young adults. Protocol: Trial registration: ClinicalTrials.gov Identifier: NCT04232475.